Nutrient-dense meal delivery in partnership with small-scale producers in Mumbai urban slums: Implementation considerations within a randomized controlled feeding trial - Huey, Samantha; Hackl, Laura; Venkatramanan, Sudha; Haas, Jere D.; Udipi, Shobha; Ghugre, Padmini (American Society for Nutrition, 2020)
Despite the multitude of evaluations of nutrition intervention trials in low-income settings, documented practice to operate such trials is scarce. We aimed to fill this gap by outlining key steps and resources required to run a small-scale intensive feeding trial such as establishing collaborations, developing an operational infrastructure, and daily orchestration of logistics for food preparation, delivery, and administration.